Role of oxygen vacancies and interstitials on structural phase transition, grain growth, and optical properties of Ga doped TiO2 - Khatun, Nasima; Tiwari, Saurabh; Vinod, C. P.; Tseng, Chuan-Ming; Liu, Shun Wei; Biring, Sajal; Sen, Somaditya (Journal of Applied Physics, 2018)
A systematic study on the effect of gallium (Ga) doping (0 <= x <= 0.10) on the structural phase transition and grain growth of TiO2 is reported here. X-ray diffraction spectroscopy and Raman spectroscopy confirm that Ga doping inhibits the phase transition. Activation energy increases from 125 kJ/mol (x = 0.00) to 300 kJ/mol (x = 0.10) upon Ga incorporation. X-ray photoelectron spectroscopy shows the presence of Ti3+/Ga3+ interstitials, substitution (Ti4+ by Ga3+), and oxygen vacancies in the samples. At lower doping (x <= 0.05), interstitials play a more significant role over substitution and oxygen vacancies, thereby resulting in a considerable lattice expansion. At higher doping (x >= 0.05), the effect of interstitials is compensated by both the effect of substitution and oxygen vacancies, thereby resulting in relatively lesser lattice expansion. Inhibition of the phase transition is the result of this lattice expansion. The crystallite size (anatase) and particle size (rutile) both are reduced due to Ga incorporation. It also modifies optical properties of pure TiO2 by increasing the bandgap (from 3.06 to 3.09 eV) and decreasing the Urbach energy (from 58.59 to 47.25 meV). This happens due to regularization of the lattice by the combined effect of substitution/ interstitials and oxygen vacancies. Published by AIP Publishing.

Ru(II)-functionalized SBA-15 as highly chemoselective, acid free and sustainable heterogeneous catalyst for acetalization of aldehydes and ketones - Lazar, Anish; Betsy, K. J.; Vinod, C. P.; Singh, A. P. (Catalysis Communications, 2018)
Combining electron deficient Ru(II) coordination sites with organofunctionalized SBA-15, (L)Ru(Il)@SBA-15, result in a mild, neutral, water scavenger free and chemo-selective acetalization catalyst for cyclic/acyclic acetals. Vacant coordination sites of ruthenium in (L)Ru(II)@SBA-15 activates protecting groups as well as reactants simultaneously and restricts the reverse acetalization reaction. Synthesized (L)Ru(Il)@SBA-15 catalyst has been thoroughly characterized and act as competitive catalyst compared to conventional acid catalysts. (L) RuaD@SBA-15 performs high catalytic activity as well as selectivity within 20 min with high TOF. The catalyst can be recycled and reaction parameters are optimized.
Keywords: Acetalization reactions; Acid free; chemo-selective; heterogeneous catalyst; Reusable; Ru(II) immobilized SBA-15

Role of Li+ and Fe3+ in modified ZnO: Structural, vibrational, opto-electronic, mechanical and magnetic properties - Bajpai, G.; Moirangthem, I.; Sarkar, S.; Barman, S. R.; Vinod, C. P.; Bajpai, S.; Riyajuddin, S.; Ghosh, K.; Basaula, D. R.; Khan, M.; Liu, S. -W.; Biring, S.; et al. (Ceramics International, 2019)
When Fe is doped in ZnO, a situation of charge imbalance is created due to the higher charge of Fe3+. A charge balance may be obtained by co-doping Li+0.5Fe3+0.5 combinations. A solid solution of Zn1-x(Fe0.5Li0.5)xO (0 ≤ x ≤ 0.03125) is synthesized with this viewpoint. The crystallites belong to a wurtzite P63mc space group, with lattice parameters a, b and c increasing nominally for x = 0.0156 and thereafter remaining invariant. The size varies in the range ~ 60–142 nm. Interstitials of Li and Zn ions are formed. Along with Fe3+ substitution these defects are reasons for O interstitials. These oxygen interstitials increase the red emission while reduction of oxygen vacancies reduces the green emission. These point defects create structural distortion and strain which can generate Zn vacancies. Bandgap reduces due to shallow defects. Mid-bandgap states due to oxygen interstitials and Fe 3d-O 2p hybridization result in NIR emission. On the other hand the crystal surface deforms due to Li addition which hardens the materials. A weak ferromagnetism appears at very low temperature which is enhanced by Li+ addition. Long range exchange mechanism between Fe3+ ions appears in the samples, mediated by magnetic polarons due to point defects.
Keywords: hardness; NIR emission; Shallow and deep level defects; Weak ferromagnetism; ZnO

Role of B site ions in bifunctional oxygen electrocatalysis: a structure-property correlation study on doped Ca(2)Fe(2)O(5)brownmillerites - Thundiyil, Shibin; Vinod, C. P.; Kurungot, Sreekumar; Devi, R. Nandini (Physical Chemistry Chemical Physics, 2020)
The role of B site doping with transition metals in brownmillerites, a perovskite related family of compounds, in bifunctional oxygen electrocatalysis,viz., simultaneous reduction and evolution reactions, is analysed. Ca2Fe1.9M0.1O5(M = Mn, Co, Ni, and Cu) is synthesised and structurally characterised by powder XRD and Rietveld refinement. Valence states of the surface B site ions are identified by X-ray photoelectron spectroscopy. Bifunctional oxygen electrochemistry is studied with the RDE and RRDE techniques and correlated with the structural and electronic parameters like oxygen non-stoichiometry and B site catalytic activity. Since the widely accepted electronic descriptors like e(g)filling may not be sufficient for explaining the bifunctional activity, B site electron donating capability as well as the extent of oxygen vacancies enhancing O(2)adsorption is also considered. Such structural parameters are also found to influence both the ORR and OER and based on this, Ni doping is proposed as advantageous for the bifunctional activity.

Role of exposed crystal facets in the atmospheric pressure CO hydrogenation on Co3O4 - Jain, Preeti; Gupta, Sharad; Vinod, C. P. (Nano-Structures & Nano-Objects, 2020)
Co3O4 nanostructures with different exposed planes are studied for atmospheric pressure CO hydrogenation. Existence of different facets is characterized by HR-TEM and found Co3O4 - NSP (nanospheres) expose (112) facet, NB (nanobelts) exhibit (110) plane and (100) is the dominant surface facet in NC (nanocubes). Different catalytic activity is demonstrated by the specific facet of Co3O4 catalysts. CO hydrogenation is facet dependent and the catalytic activity follows the order of Co3O4-NB > Co3O4-NC > Co3O4-NSP.

Role of metal-support interaction for atmospheric pressure CO2 hydrogenation over Pd/(Ti)-SBA-15 catalyst: effect of titanium composition on products selectivity - Soni, Yogita; Gupta, Sharad; Vinod, C. P. (Molecular Catalysis, 2021)
The potential role of metal-support interaction for tuning the product selectivity during atmospheric pressure CO2 hydrogenation has been demonstrated on Pd/(Ti)-SBA-15 catalyst. Highly dispersed Pd NPs on SBA-15 (Pd/ SBA-15) was synthesized and further modified with titanium of varying composition. Comparison of catalytic activity of Pd/Ti-SBA-15 with its counterparts (Pd/SBA-15 and Pd/TiO2) illustrated the significance of strong PdTi interface in this catalyst and its role in tuning the product selectivity of CO2 hydrogenation. The generation of an ample amount of oxygen vacancies in the Pd/Ti-SBA-15 catalyst with maximum metallic Pd sites in close vicinity of Ti is proposed to boost the CO2 hydrogenation activity.
Keywords: CO2 hydrogenation; Metal-support interaction; Modified deposition precipitation; oxygen vacancies; Titanosilicates